Lifting the banking veil: Credit standards' harmonization through lending transparency - Jung Koo Kang; Maria Loumioti; Regina Wittenberg Moerman (European Central Bank (ECB), 2020)
We explore whether the transparency in banks' lending activities enhances the harmonization of credit terms that a bank offers across its different geographic regions. We take advantage of a novel loan-level reporting initiative by the European Central Bank, which requires repo borrowing banks that pledge their asset-backed securities as collateral to disclose granular information on loan characteristics and performance. We find that loans originated under the transparency regime share more similar interest rate, loan-to-collateral-value ratio and maturity compared to same-purpose loans issued by the same bank in different regions. Underperforming regional branches and those with less easily accessible peer-branches experience greater convergence in their credit terms, suggesting that transparency facilitates learning across a bank's different geographic regions. Additionally, banks that face stronger regulatory scrutiny are more likely to alleviate credit term disparities under the transparency regime. Overall, our findings suggest that transparency enhances the within-bank harmonization of lending practices.
Keywords: M41; G21; D83; 330; transparency; harmonization; credit market; learning; regulatory scrutiny